Pattern of Cervical Spine Injuries in Karnali Province Of Nepal- A Cross Sectional Study - Jha, Prabhat; Khadka, Nilam (Nepal Journal of Neuroscience, 2025)
Introduction Cervical spine injury is a common occurrence in trauma patients. Materials and Methods This is a descriptive cross sectional study performed over a period of 6 months in Province Hospital, Surkhet. This study describes the incidence, presentation, management of cervical spine injury in Province Hospital Surkhet over a 6 month period.Results A total of 29 patients with cervical spine injury were admitted in Province Hospital, Surkhet over a 6 month period. Most commonly injuries occurred in the second and third decades with male predominance. Diagnosis was done using computed tomography and magnetic resonance imaging. Ten cases underwent surgery and the other cases were managed conservatively.Conclusion Cervical spine injury is a common presentation after trauma. It can be dealt with efficiently if a protocol based management is done.